Semiconductor processing tape
Patent Information
- Application Number
- JP2021565581
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-17
- Filing Date
- 2020-12-15
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2040-12-15
AI Technical Summary
【0011】 本発明によれば、十分な凹凸吸収性、適度な粘着力、帯電防止性能を有し、かつ半導体加工用テープを剥離した後に糊残りが生じにくい半導体加工用テープを提供できる。
Smart Images

Figure 0007632304000001 
Figure 0007632304000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a tape for semiconductor processing. [Background technology]
[0002] In response to the demand for thinner semiconductor devices, a backgrinding process is carried out in the manufacturing process of semiconductor devices. In the backgrinding process, the front surface of the semiconductor wafer is protected with a backgrinding tape, and then the back surface of the semiconductor wafer is ground to thin the semiconductor wafer. This application claims priority based on Japanese Patent Application No. 2019-227280, filed on December 17, 2019, the contents of which are incorporated herein by reference.
[0003] Conventionally, various backgrind tapes have been proposed for use in protecting the surface of a semiconductor wafer. In recent years, there has been a demand for backgrind tapes that have sufficient unevenness absorption properties for semiconductor wafers having uneven surfaces, such as semiconductor wafers having bumps (electrodes) made of solder or the like formed on the surface.
[0004] Conventionally, when a backgrind tape is peeled off from a semiconductor wafer, static electricity called peeling electrification is generated, which may destroy the circuit of the semiconductor wafer or cause foreign matter to adhere to the semiconductor wafer. For this reason, a backgrind tape is required to have sufficient antistatic properties.
[0005] It is believed that treatment to prevent peeling static electricity is effective when applied to the adhesive side. However, when antistatic materials such as surfactants, conductive fillers, and carbon black are added to the adhesive itself, the physical properties of the adhesive change. In addition, it becomes difficult to adjust or suppress the adhesive properties and their change over time. Furthermore, when peeling off the adhesive tape, the adhesive or the added antistatic material itself may migrate to the adherend and contaminate the adherend. In this case, visible glue residue, adhesion of microscopic particles, or adhesion of optically unobservable liquid matter may occur on the surface of the adherend, which may have adverse effects such as poor adhesion of parts in subsequent processes.
[0006] Against this background, for example, Patent Document 1 discloses an adhesive film for semiconductor wafer processing that is a backgrind tape that combines both irregularity absorbency and antistatic properties, and that comprises, in that order, a base layer, an irregularity-absorbing resin layer, an antistatic layer, and an adhesive resin layer. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2018-6540 A Summary of the Invention [Problem to be solved by the invention]
[0008] However, the adhesive film for semiconductor wafer processing described in Patent Document 1 requires each layer to be formed into a sheet and then laminated together, which makes the manufacturing procedure complicated. In addition, the backgrind tape is required to have an adhesive strength that can fix an adherend such as a semiconductor wafer to the backgrind tape with sufficient strength. However, if a backgrind tape with high adhesive strength is applied to an adherend, the adherend is processed, and then the backgrind tape is peeled off, the adhesive layer of the backgrind tape may be transferred to the adherend, resulting in adhesive residue.
[0009] The present invention has been made in consideration of the above circumstances, and has an object to provide a semiconductor processing tape which has sufficient unevenness absorbency, appropriate adhesive strength, and antistatic performance, is less likely to leave adhesive residue after being peeled off, and can be manufactured with fewer manufacturing steps. [Means for solving the problem]
[0010] The present invention includes the following aspects. [1] A semiconductor processing tape comprising a sheet-like substrate having a substrate body and an antistatic layer provided on at least one side of the substrate body, and a pressure-sensitive adhesive layer formed on the antistatic layer, the antistatic layer contains a polypyrrole compound, The pressure-sensitive adhesive layer is a cured product of a pressure-sensitive adhesive composition, The thickness of the pressure-sensitive adhesive layer is 50 to 500 μm, The pressure-sensitive adhesive composition includes a polyurethane (A), a (meth)acrylate monomer (B), a chain transfer agent (C), and a photopolymerization initiator (D), The polyurethane (A) contains polyurethane (a1), the polyurethane (a1) has a skeleton containing a structure derived from a polyoxyalkylene polyol and a structure derived from a polyisocyanate, and has (meth)acryloyl groups at a plurality of terminals; A tape for semiconductor processing, characterized in that the (meth)acrylate monomer (B) contains a monofunctional (meth)acrylate and a polyfunctional (meth)acrylate. [2] The semiconductor processing tape according to [1], wherein the pressure-sensitive adhesive layer has a single layer structure. [3] The semiconductor processing tape according to [1] or [2], wherein the chain transfer agent (C) is a polyfunctional thiol. [4] The tape for semiconductor processing according to any one of [1] to [3], wherein the pressure-sensitive adhesive layer has a gel fraction of 50 to 65 mass %. [5] The surface resistivity of the pressure-sensitive adhesive layer is 1×10 12 The tape for semiconductor processing according to any one of [1] to [4], wherein the resistivity is less than Ω / □. [6] The semiconductor processing tape according to any one of [1] to [5], wherein the (meth)acrylate monomer (B) contains 85 to 99 mol % of the monofunctional (meth)acrylate and 1 to 15 mol % of the polyfunctional (meth)acrylate. [7] The pressure-sensitive adhesive composition, 20 to 50% by mass of the polyurethane (A), 35 to 79% by mass of the (meth)acrylate monomer (B), The chain transfer agent (C) is 0.5 to 8% by mass, The tape for semiconductor processing according to any one of [1] to [6], comprising 0.01 to 5 mass % of the photopolymerization initiator (D). [8] The tape for semiconductor processing according to any one of [1] to [7], wherein the pressure-sensitive adhesive composition further contains a fatty acid ester (E). Effect of the Invention
[0011] According to the present invention, it is possible to provide a semiconductor processing tape which has sufficient unevenness absorbency, appropriate adhesive strength, and antistatic performance, and which is less likely to leave adhesive residue after being peeled off.
[0012] Moreover, the semiconductor processing tape of the present invention has an adhesive layer which is a cured product of an adhesive composition and has sufficient unevenness absorbency and adhesive strength, so that it is not necessary to separately provide a layer having unevenness absorbency and a layer having adhesive strength, and it can be manufactured with fewer manufacturing steps. Furthermore, by forming the adhesive layer on a substrate having an antistatic layer, it is possible to obtain sufficient antistatic performance. Therefore, the semiconductor processing tape of the present invention is suitable as a backgrinding tape used to protect the surface during the backgrinding process of an adherend having an uneven surface, such as a semiconductor wafer having bumps formed on its surface. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, embodiments of the present invention will be described in detail, however, the present invention is not limited to the embodiments described below.
[0014] <Tape for semiconductor processing> The semiconductor processing tape in this embodiment has a sheet-like substrate and a pressure-sensitive adhesive layer formed on one side of the substrate. The substrate has a substrate body and an antistatic layer provided on at least one side of the substrate body. The antistatic layer contains a polypyrrole compound. The pressure-sensitive adhesive layer is a cured product of a pressure-sensitive adhesive composition described below. The pressure-sensitive adhesive layer has a thickness of 50 to 500 μm. The pressure-sensitive adhesive composition contains polyurethane (A), a (meth)acrylate monomer (B), a chain transfer agent (C), and a photopolymerization initiator (D). The polyurethane (A) contains polyurethane (a1). The polyurethane (a1) has a skeleton containing a structure derived from a polyoxyalkylene polyol and a structure derived from a polyisocyanate, and has (meth)acryloyl groups at a plurality of ends. The (meth)acrylate monomer (B) contains a monofunctional (meth)acrylate and a polyfunctional (meth)acrylate. It should be noted that the "tape" referred to here is not limited to strip-shaped tapes, but also includes rectangular or circular sheets.
[0015] (Substrate body) The material of the substrate body can be appropriately selected, and examples thereof include resin materials. Examples of resin materials include polyolefins such as polyethylene (PE) and polypropylene (PP); polyester sheets such as polyethylene terephthalate (PET), polybutylene terephthalate (PBT), and polyethylene naphthalate; polyvinyl chloride (PVC); polyimide (PI); polyphenylene sulfide (PPS); ethylene vinyl acetate (EVA); and polytetrafluoroethylene (PTFE). Among these resin materials, it is preferable to use PE, PP, and PET, since a sheet having appropriate flexibility can be obtained. The resin materials may be used alone or in combination of two or more.
[0016] When a resin sheet made of a resin material is used as the substrate main body, the resin sheet may be a single layer or a multi-layer structure of two or more layers (e.g., a three-layer structure). In a resin sheet having a multi-layer structure, the resin material constituting each layer may be a resin material containing only one type alone or a resin material containing two or more types.
[0017] Furthermore, the surface of the substrate body on which the antistatic layer is formed may be subjected to an adhesion enhancing treatment such as an acid treatment, an alkali treatment, a primer treatment, a corona treatment, a plasma treatment, an ultraviolet treatment or an ozone treatment, if necessary.
[0018] The thickness of the substrate body can be appropriately selected depending on the material of the substrate body. When the semiconductor processing tape is applied to a semiconductor wafer having an uneven surface and then peeled off, or when the semiconductor processing tape uses a resin sheet as the substrate body, the thickness of the substrate body is preferably 10 to 1000 μm, more preferably 50 to 300 μm. When the thickness of the substrate body is 10 μm or more, the rigidity (stiffness) of the semiconductor processing tape is high. Therefore, when the semiconductor processing tape is applied to or peeled off from the semiconductor wafer, which is the adherend, wrinkles and lifting tend not to occur in the semiconductor processing tape. In addition, when the thickness of the substrate body is 1000 μm or less, the semiconductor processing tape applied to the semiconductor wafer is easily peeled off from the semiconductor wafer, and the workability (handling ability, handling) is improved.
[0019] (Antistatic layer) At least one side of the substrate body has an antistatic layer. The antistatic layer contains a polypyrrole compound. The polypyrrole compound is not particularly limited as long as it is a polymer of pyrrole and / or a pyrrole derivative, and may contain a small amount of other monomers other than pyrrole and pyrrole derivatives as polymerization components. Examples of pyrrole derivatives include N-alkylpyrrole, 3-alkylpyrrole, 3,4-dialkylpyrrole, 3-alkoxypyrrole, 3,4-dialkoxypyrrole, 3-chloropyrrole, and 3,4-dichloropyrrole. By having an antistatic layer containing a polypyrrole compound, the antistatic effect of the semiconductor processing tape becomes stable over time and has good non-contamination properties.
[0020] The means for providing the antistatic layer is not particularly limited, and various known methods can be used, for example, the following methods (i) to (vi). (i) A method in which pyrrole and / or a pyrrole derivative is dissolved in an organic solvent such as diethyl ether, methanol, or tetrahydrofuran (THF), applied to a substrate body, and then the organic solvent is dried and removed (e.g., Japanese Patent Application Laid-Open No. 3-122115); (ii) a method in which pyrrole and / or a pyrrole derivative is applied to a substrate body, and then the substrate body is immersed in an organic solvent of a salt or acid, water or a mixture thereof for doping, and then the solvent is dried and removed (e.g., JP-A-4-285626); (iii) A method in which the surface of a substrate body is coated with polypyrrole by polymerizing a pyrrole monomer in a treatment solution containing the substrate body in the presence of a chemical oxidation polymerization catalyst and a dopant according to a chemical oxidation polymerization method (e.g., JP-A-2000-280335); (iv) A method in which an aqueous solution containing fine particles surface-coated with pyrrole and / or a pyrrole derivative is applied to the surface of a substrate body, and the applied solution is stretched after drying (e.g., JP-A-8-58044); (v) a method in which a layer containing polypyrrole and / or a polypyrrole derivative, an organic electron acceptor, and a thermoplastic resin is laminated on the surface of a substrate body (e.g., JP-A-10-278188); (vi) A method in which fine particles of polypyrrole and / or a polypyrrole derivative are dispersed in a hydrophilic solvent using a polymer dispersant and / or a dopant, and then mixed with a hydrophilic binder resin to prepare a resin composition; the resin composition is applied onto a substrate body such as a polymer film, and the solvent is then dried and removed to form a film (e.g., JP 2001-334598 A).
[0021] Among them, from the viewpoint of adhesion to the substrate body and adhesion to the adhesive layer, the method of "(vi) dispersing fine particles of polypyrrole and / or polypyrrole derivative in a hydrophilic solvent using a polymer dispersant and / or a dopant, and further mixing with a water-soluble or water-dispersible binder resin to prepare a resin composition, applying the resin composition onto the substrate body, and then drying and removing the solvent to form a film" is preferred. For example, a known coating method such as a bar coater, air knife coater, blade coater, rod coater, gravure coater, size press coater, or gate roll coater may be used.
[0022] The thickness of the antistatic layer is preferably 0.1 to 20 μm, and more preferably 0.5 to 10 μm. If the thickness of the antistatic layer is within this range, sufficient antistatic performance is exhibited. The content of the polypyrrole compound in the antistatic layer is preferably 5 to 80 mass %, and more preferably 10 to 70 mass %. If it is 5 mass % or more, sufficient antistatic performance is obtained, and if it is 80 mass % or less, economic efficiency is also good.
[0023] Specific examples of the polymer dispersant include polymer acids, salts of these polymer acids, and esters of these polymer acids, and these may be used alone or in combination of two or more. Specific examples of the polymer acids include polymer acids such as polystyrene sulfonic acid, polyacrylic acid, polyallyl sulfonic acid, and alginic acid. Specific examples of the salts of the polymer acids include neutralized salts such as sodium salts, potassium salts, and ammonium salts. The dopant is not particularly limited, but it is preferable to use molecular iodine and / or iodine ions. When iodine ions are used, the iodine ion valence is not particularly specified. By using iodine and / or iodine ions, the electrical conductivity and adhesion to the substrate body are further improved.
[0024] Examples of the water-soluble or water-dispersible binder resin include polyester, polyurethane, acrylic resin, vinyl resin, epoxy resin, and amide resin. These may have a substantially composite structure due to copolymerization of each skeletal structure. Examples of the binder resin having a composite structure include acrylic resin graft polyester, acrylic resin graft polyurethane, vinyl resin graft polyester, and vinyl resin graft polyurethane. By containing these resins, the strength of the antistatic layer and the adhesion to the substrate body can be improved. The water-soluble or water-dispersible binder resin may be used alone or in combination of two or more kinds.
[0025] The resin composition may also contain a crosslinking reactive compound as necessary. The crosslinking reactive compound can improve the cohesiveness, surface hardness, scratch resistance, solvent resistance, and water resistance of the coating layer mainly by crosslinking with functional groups contained in other resins or compounds, or by self-crosslinking. As the crosslinking reactive compound that can be used, amino resins such as melamine-based, benzoguanamine-based, and urea-based, oxazoline-based, epoxy-based, and glyoxal-based, etc. are preferably used. Polymer-type crosslinking reactive compounds having reactive groups on other polymer skeletons are also included.
[0026] The resin composition may contain additives such as surfactants, defoamers, coatability improvers, thickeners, organic lubricants, organic particles, inorganic particles, antioxidants, ultraviolet absorbers, dyes, pigments, etc. These additives may be used alone or in combination of two or more kinds, if necessary.
[0027] (Adhesive layer) The pressure-sensitive adhesive layer is formed on the antistatic layer of the substrate. When antistatic layers are formed on both sides of the substrate body, an adhesive layer is formed on one of the surfaces.
[0028] The adhesive layer is a cured product of the adhesive composition described later. The adhesive layer is particularly a photocured product of the adhesive composition described later. The semiconductor processing tape may be used in applications where it is attached to an adherend such as a semiconductor wafer having an uneven surface and then peeled off. In that case, the adhesive layer has a role of protecting the surface of the adherend during the back grinding process by fixing the semiconductor processing tape to the surface of the adherend with sufficient adhesive strength. In addition, the adhesive layer has a role of improving the accuracy of the back grinding process by absorbing and smoothing the unevenness of the adherend surface. Furthermore, the adhesive layer reduces the peeling charge generated when the semiconductor processing tape is peeled off from the adherend. In addition, the adhesive layer of the semiconductor processing tape of this embodiment does not leave any adhesive residue when the semiconductor processing tape is peeled off.
[0029] The thickness of the adhesive layer in this embodiment is 50 to 500 μm, preferably 60 to 400 μm, and more preferably 70 to 300 μm. When the thickness of the adhesive layer is 50 μm or more, the unevenness absorption property and adhesive strength of the semiconductor processing tape are good. In addition, when the thickness of the adhesive layer is 500 μm or less, the thickness control of the adhesive layer is easy.
[0030] When the semiconductor processing tape of this embodiment is applied to an adherend having an uneven surface, the thickness of the adhesive layer is largely dependent on the height of the uneven surface of the adherend. The thickness of the adhesive layer is preferably equal to or greater than the height of the uneven surface so as to obtain sufficient unevenness absorption. Therefore, for example, when the uneven surface is a bump formed on a semiconductor wafer, the thickness of the adhesive layer is preferably at least twice the height of the bump. The height of the bump is usually 30 to 200 μm. For example, when the bump height is 100 μm, the thickness of the adhesive layer is preferably at least 200 μm, and when the bump height is 200 μm, the thickness of the adhesive layer is preferably at least 400 μm.
[0031] The adhesive layer may be a single layer structure, or may be a multilayer structure in which the adhesive layer of this embodiment and one or more other adhesive layers different from the adhesive layer of this embodiment are laminated. As the other adhesive layer, a conventionally known adhesive layer can be used. In this embodiment, when the adhesive layer has a multilayer structure, the adhesive layer of this embodiment must be present on the outermost surface. In addition, in the semiconductor processing tape of this embodiment, a layer other than the adhesive layer may be present between the adhesive layer and the substrate within a range that does not inhibit the curing of the adhesive layer. In terms of shortening the process, the adhesive layer is preferably a single layer structure.
[0032] The gel fraction of the pressure-sensitive adhesive layer is preferably 50 to 65% by mass. When the gel fraction is 50% by mass or more, the occurrence of adhesive residue caused by peeling off the semiconductor processing tape attached to the adherend can be more effectively suppressed. When the gel fraction is 65% by mass or less, the pressure-sensitive adhesive layer has sufficient fluidity, and the unevenness absorbency of the semiconductor processing tape becomes even better. The gel fraction of the pressure-sensitive adhesive layer is more preferably 52% by mass or more. The gel fraction of the pressure-sensitive adhesive layer is more preferably 63% by mass or less. The gel fraction of the pressure-sensitive adhesive layer can be achieved in a preferred range, for example, by adjusting the composition of the pressure-sensitive adhesive composition described below to fall within a preferred range.
[0033] (Measurement of gel fraction of adhesive layer) The gel fraction of the adhesive layer is measured by the following method. First, a sheet of about 1 g size is cut out from the semiconductor processing tape, and the adhesive layer is peeled off from the substrate to prepare a measurement sample, and its mass is measured. Next, the measurement sample is immersed in 50 ml of toluene and left at room temperature for 72 hours. After that, the measurement sample is taken out of the toluene, dried at 80°C for 5 hours, and the mass is measured again. Then, the gel fraction is calculated based on the following formula. Gel fraction (%) = [A / B] x 100 A: Mass of the measurement sample after immersion in toluene (excluding the mass of toluene) B: Mass of the measurement sample before immersion in toluene
[0034] The surface resistivity of the adhesive layer is 1×10 12 It is preferable that the resistance is less than 1×10 11 It is more preferable that the surface resistivity is less than 1×10 12 If it is less than Ω / □, peeling static electricity generated when the semiconductor processing tape attached to an adherend is peeled off is reduced, resulting in a semiconductor processing tape with even better antistatic performance.
[0035] The semiconductor processing tape may have a transparent separator on the surface of the adhesive layer for the purpose of protecting the adhesive layer. The separator is preferably laminated on the surface of the adhesive layer. For example, paper, plastic film, etc. can be used as the material of the separator, and it is preferable to use a plastic film from the viewpoint of excellent surface smoothness. The plastic film used as the separator is not particularly limited as long as it can protect the above-mentioned adhesive layer, and examples thereof include polyethylene, polypropylene, polyethylene terephthalate, polybutene, etc.
[0036] <Adhesive composition> The adhesive layer of the semiconductor processing tape of this embodiment is a cured product of an adhesive composition. The adhesive composition used as the material of the adhesive layer in the semiconductor processing tape of this embodiment will be described in detail below. The pressure-sensitive adhesive composition of the present embodiment contains a polyurethane (A), a (meth)acrylate monomer (B), a chain transfer agent (C), and a photopolymerization initiator (D).
[0037] (Polyurethane (A)) The polyurethane (A) contains a polyurethane (a1) described below. The polyurethane (A) may contain not only the polyurethane (a1) but also a polyurethane (a2) described below for the purpose of adjusting the cohesive strength of the cured product of the pressure-sensitive adhesive composition. It is preferable that the polyurethane (A) does not contain any components other than the polyurethane (a1) and the polyurethane (a2) contained as necessary.
[0038] [Polyurethane (a1)] The polyurethane (a1) has a skeleton containing a structure derived from a polyoxyalkylene polyol and a structure derived from a polyisocyanate. The polyurethane (a1) also has (meth)acryloyl groups at a plurality of terminals. The (meth)acryloyl groups at the terminals of the polyurethane (a1) are preferably part of a (meth)acryloyloxy group.
[0039] In the present invention, "multiple ends" of a polyurethane refers to two ends when the polyurethane is a linear polymer, and refers to two or more ends out of the same number of ends as the number of branched chains when the polyurethane is a branched polymer. In the present invention, the (meth)acryloyl group means one or more groups selected from a functional group represented by the chemical formula CH2=CH-CO- and a functional group represented by the chemical formula CH2=C(CH3)-CO-.
[0040] [Polyurethane (a2)] Like polyurethane (a1), polyurethane (a2) has a skeleton containing a structure derived from a polyoxyalkylene polyol and a structure derived from a polyisocyanate. Unlike polyurethane (a1), polyurethane (a2) has a (meth)acryloyl group at only one end. The (meth)acryloyl group at the end of polyurethane (a2) is preferably a part of a (meth)acryloyloxy group. In polyurethane (a2), the end not having a (meth)acryloyl group preferably has one selected from the group consisting of an isocyanato group, a structure derived from an alkyl alcohol, and a structure derived from an alkyl isocyanate, and more preferably has a structure derived from an alkyl alcohol.
[0041] "Polyoxyalkylene polyol-derived structure" The polyoxyalkylene polyol having a structure derived from polyoxyalkylene polyol contained in the skeleton of polyurethane (a1) and polyurethane (a2) preferably has an alkylene chain having 2 to 4 carbon atoms. Specific examples include polyoxyethylene polyol, polyoxypropylene polyol, polyoxybutylene polyol, etc.
[0042] The polyoxyalkylene polyol having a structure derived from a polyoxyalkylene polyol may contain one type of alkylene chain, or may contain two or more types of alkylene chains. The polyoxyalkylene polyol having a structure derived from polyoxyalkylene polyol is preferably one having two or three hydroxyl groups at the terminals (diol-type or triol-type polyoxyalkylene polyol), more preferably a polyoxyalkylene glycol (diol-type), and particularly preferably a polypropylene glycol having an alkylene chain with three carbon atoms.
[0043] For example, when the polyoxyalkylene polyol is polypropylene glycol, the hydroxyl value is preferably 20 to 120 mgKOH / g, more preferably 30 to 100 mgKOH / g, and even more preferably 40 to 80 mgKOH / g. Specific examples of polypropylene glycol include polypropylene glycol having a hydroxyl group (hydroxy group) at the end and a hydroxyl value of 56 mgKOH / g (Actocol D-2000; Mitsui Chemicals, number average molecular weight 2000, diol type).
[0044] Here, the hydroxyl value of polyoxyalkylene polyol is the hydroxyl value of polyoxyalkylene polyol measured according to JIS K0070. That is, it means the number of milligrams of potassium hydroxide required to neutralize free acetic acid when 1 g of polyoxyalkylene polyol is acetylated. Specifically, it can be determined by acetylating the hydroxyl groups in a sample (polyoxyalkylene polyol) using acetic anhydride and titrating the free acetic acid generated at that time with a potassium hydroxide solution.
[0045] The number average molecular weight of the polyoxyalkylene polyol is preferably 500 to 5,000, more preferably 800 to 4,000, and even more preferably 1,000 to 3,000. When the number average molecular weight of the polyoxyalkylene polyol is 500 or more, the semiconductor processing tape having the adhesive layer which is the cured product of the adhesive composition containing the polyurethane (A) synthesized using the polyoxyalkylene polyol has high peel strength. In addition, when the number average molecular weight of the polyoxyalkylene polyol is 5,000 or less, the polyurethane (A) synthesized using the polyoxyalkylene polyol contains a sufficient amount of urethane bonds. Therefore, the cured product obtained by curing the adhesive composition containing the polyurethane (A) has good cohesion.
[0046] The structure derived from the polyoxyalkylene polyol contained in the skeleton of the polyurethane (a1) and the polyurethane (a2) may each be of only one type, or may be of two or more types. The polyurethane (a1) and the polyurethane (a2) may have a structure in which structures derived from two or more different polyoxyalkylene polyols are bonded via a structure derived from a polyisocyanate. The structure derived from a polyoxyalkylene polyol contained in the skeleton of the polyurethane (a1) and the structure derived from a polyoxyalkylene polyol contained in the skeleton of the polyurethane (a2) may be the same as or different from each other.
[0047] "Polyisocyanate-derived structure" As the polyisocyanate having the polyisocyanate-derived structure contained in the skeleton of the polyurethane (a1) and polyurethane (a2), a compound having a plurality of isocyanate groups is used, and it is preferable to use a diisocyanate. Examples of diisocyanates include tolylene diisocyanate and hydrogenated products thereof, xylylene diisocyanate and hydrogenated products thereof, diphenylmethane diisocyanate and hydrogenated products thereof, 1,5-naphthylene diisocyanate and hydrogenated products thereof, hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, tetramethylxylylene diisocyanate, isophorone diisocyanate, 4,4'-dicyclohexyl diisocyanate, 1,3-bis(isocyanatemethyl)cyclohexane, and norbornane diisocyanate.
[0048] Among these polyisocyanates, it is preferable to use a hydrogenated product of isophorone diisocyanate or diphenylmethane diisocyanate from the viewpoint of controlling the light resistance of the polyurethane (A) synthesized using the polyisocyanate and the reactivity with polyoxyalkylene polyol. Also, it is more preferable to use a hydrogenated product of diphenylmethane diisocyanate from the viewpoint of the reactivity with polyoxyalkylene polyol.
[0049] Specific examples of polyisocyanates having a polyisocyanate-derived structure include hydrogenated diphenylmethane diisocyanate (Desmodur W, manufactured by Sumika Covestro Urethane Co., Ltd.) and isophorone diisocyanate (Desmodur I, manufactured by Sumika Covestro Urethane Co., Ltd.).
[0050] The polyisocyanate-derived structure contained in the skeleton of each of the polyurethane (a1) and the polyurethane (a2) may be of only one type, or may be of two or more types. Furthermore, the structure derived from a polyisocyanate contained in the skeleton of the polyurethane (a1) and the structure derived from a polyisocyanate contained in the skeleton of the polyurethane (a2) may be the same as or different from each other.
[0051] It is preferable that the polyisocyanate-derived structure and the polyoxyalkylene polyol-derived structure contained in the skeletons of the polyurethane (a1) and the polyurethane (a2) are the same, because in this case, the polyurethane (a1) and the polyurethane (a2) can be synthesized simultaneously, and the polyurethane (A) can be produced efficiently.
[0052] The proportion of the polyurethane (a1) contained in the polyurethane (A) is preferably 80 to 100%, more preferably 90 to 100%, and even more preferably 100%, of the polyurethane (A) in terms of the number of molecules. The proportion of polyurethane (a2) contained in polyurethane (A) is preferably 0 to 20%, more preferably 0 to 10%, and even more preferably 0%, of polyurethane (A) in terms of the number of molecules. When the proportion of polyurethane (a1) contained in polyurethane (A) is 80% or more, the cured product of the pressure-sensitive adhesive composition containing polyurethane (A) has sufficiently high cohesive strength, which is preferable.
[0053] Of the total number of terminals contained in polyurethane (A) (the total number of terminals of polyurethane (a1) and polyurethane (a2) contained as necessary), it is preferable that a (meth)acryloyl group is introduced into 90 to 100% on a molecular number basis, more preferably 95 to 100%, and even more preferably 100%. When the amount of (meth)acryloyl groups introduced into the total number of terminals contained in polyurethane (A) is 90% or more on a molecular number basis, the cohesive strength of the cured product obtained by curing the pressure-sensitive adhesive composition containing polyurethane (A) is sufficiently high.
[0054] The ratio of the number of terminals into which a (meth)acryloyl group is introduced, based on the number of molecules, to the total number of terminals contained in the polyurethane (A) can be calculated using the results of analyzing the polyurethane (A). Examples of the analysis method include infrared absorption spectroscopy (IR) and nuclear magnetic resonance spectroscopy (NMR).
[0055] The ratio of the contents of polyurethane (a1) and polyurethane (a2) contained in polyurethane (A), i.e., the ratio of the number of terminals into which a (meth)acryloyl group has been introduced on a molecular basis to the total number of terminals contained in polyurethane (A), can be adjusted by the production method of polyurethane (A) described later.
[0056] The weight average molecular weight of the polyurethane (A) is preferably 30,000 to 200,000, more preferably 50,000 to 150,000, and even more preferably 60,000 to 100,000. When the weight average molecular weight of the polyurethane (A) is 30,000 or more, the cured product obtained by curing the pressure-sensitive adhesive composition containing the polyurethane (A) has good flexibility. When the weight average molecular weight of the polyurethane (A) is 200,000 or less, the pressure-sensitive adhesive composition containing the polyurethane (A) is easy to handle and has good workability.
[0057] (Method for measuring mass average molecular weight of polyurethane (A)) The weight average molecular weight of the polyurethane (A) is a value calculated in terms of polystyrene measured by gel permeation chromatography (GPC-101; Shodex (registered trademark) manufactured by Showa Denko K.K.) (hereinafter referred to as GPC). The measurement conditions for GPC are as follows. Column: LF-804 (Showa Denko K.K.) Column temperature: 40℃ Sample: 0.2% by mass solution of polyurethane (A) in tetrahydrofuran Flow rate: 1ml / min Eluent: Tetrahydrofuran Detector: RI detector (differential refractive index detector)
[0058] The content of polyurethane (A) in the pressure-sensitive adhesive composition of this embodiment is preferably 20 to 50% by mass, more preferably 25 to 45% by mass, and even more preferably 30 to 40% by mass. When the content of polyurethane (A) is 20% by mass or more, the cured product obtained by curing the pressure-sensitive adhesive composition has sufficient cohesive strength and excellent adhesive strength. In addition, in a semiconductor processing tape using this cured product as a pressure-sensitive adhesive layer, the softness of the pressure-sensitive adhesive layer is in an appropriate range, and air bubbles are unlikely to be trapped between the pressure-sensitive adhesive layer and the adherend. In addition, when the content of polyurethane (A) is 50% by mass or less, the cured product obtained by curing the pressure-sensitive adhesive composition has sufficient flexibility. Therefore, a semiconductor processing tape using this cured product as a pressure-sensitive adhesive layer has good wettability to the adherend.
[0059] ((Meth)acrylate Monomer (B)) The (meth)acrylate monomer (B) is other than the polyurethane (A) and contains a monofunctional (meth)acrylate and a polyfunctional (meth)acrylate.
[0060] In the present invention, the term "monofunctional" in the monofunctional (meth)acrylate means a (meth)acrylate having only one (meth)acryloyloxy group. In the present invention, the term "polyfunctional" in the polyfunctional (meth)acrylate means a (meth)acrylate having two or more (meth)acryloyloxy groups.
[0061] As the (meth)acrylate monomer (B), from the viewpoint of the cohesive strength of the cured product obtained by curing the adhesive composition and the curability of the adhesive composition, it is preferable to use a combination of a monofunctional (meth)acrylate and a polyfunctional (meth)acrylate. It is more preferable to contain a monofunctional (meth)acrylate and a trifunctional or higher (meth)acrylate. In particular, it is most preferable to contain a monofunctional (meth)acrylate and a trifunctional (meth)acrylate having three (meth)acryloyloxy groups.
[0062] Examples of monofunctional (meth)acrylates include alkyl (meth)acrylates, cyclic alkyl (meth)acrylates such as isobornyl (meth)acrylate, alkoxyalkyl (meth)acrylates, alkoxy(poly)alkylene glycol (meth)acrylates, hydroxyl group-containing (meth)acrylates, carboxyl group-containing (meth)acrylates, fluorinated alkyl (meth)acrylates, dialkylaminoalkyl (meth)acrylates, (meth)acrylamides, epoxy group-containing (meth)acrylates, (meth)acryloylmorpholine, etc. These may be used alone or in combination of two or more.
[0063] Among these monofunctional (meth)acrylates, it is preferable to contain an alkyl (meth)acrylate. This is because the adhesive strength (peeling strength) and gel fraction of the cured product obtained by curing the adhesive composition tend to be in a more appropriate range when the cured product is used as an adhesive layer of a semiconductor processing tape. As the alkyl (meth)acrylate, it is more preferable to use an alkyl (meth)acrylate having an alkyl group having 4 to 10 carbon atoms. Specifically, examples of the alkyl (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. Among these, it is particularly preferable to use 2-ethylhexyl (meth)acrylate and / or n-butyl (meth)acrylate.
[0064] The polyfunctional (meth)acrylate is a compound having a plurality of (meth)acryloyloxy groups other than the polyurethane (A). As the polyfunctional (meth)acrylate, it is preferable to use a poly(meth)acrylate of a polyol compound. Specific examples of polyfunctional (meth)acrylates include polyethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, hydroxypivalic acid ester neopentyl glycol di(meth)acrylate, 1,3-bis(hydroxyethyl)-5,5-dimethylhydantoin di(meth)acrylate, α,ω-di(meth)acryl bisdiethylene glycol phthalate, trimethylolpropane tri(meth)acrylate, ethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, diacryloxyethyl phosphate, and pentaerythritol tetra(meth)acrylate. Among these, it is preferable to use trimethylolpropane tri(meth)acrylate as the polyfunctional (meth)acrylate from the viewpoint of curing property of the pressure-sensitive adhesive composition. These polyfunctional (meth)acrylates may be used alone or in combination of two or more.
[0065] The ratio of the monofunctional (meth)acrylate and the polyfunctional (meth)acrylate is preferably 85 to 99 mol % of the monofunctional (meth)acrylate and 1 to 15 mol % of the polyfunctional (meth)acrylate when the total of the (meth)acrylate monomers (B) is taken as 100 mol %. In this case, the content of the monofunctional (meth)acrylate is more preferably 90 to 99 mol %, and even more preferably 95 to 98 mol %. The content of the polyfunctional (meth)acrylate is more preferably 1 to 10 mol %, and even more preferably 2 to 5 mol %.
[0066] When the content of monofunctional (meth)acrylate is 85 mol% or more, the fluidity of the cured product obtained by curing the adhesive composition is in a preferred range when the cured product is used as an adhesive layer of a semiconductor processing tape. Therefore, the semiconductor processing tape using this cured product as an adhesive layer has sufficient unevenness absorption properties, and when it is applied to an adherend having uneven parts on the surface, it is preferable that gaps are unlikely to occur between the uneven parts of the adherend. In addition, when the content of monofunctional (meth)acrylate is 99 mol% or less, the semiconductor processing tape using the cured product of the adhesive composition as an adhesive layer is unlikely to leave adhesive residue when peeled off from the adherend, which is preferable.
[0067] When the content of the polyfunctional (meth)acrylate is 1 mol% or more, the fluidity of the cured product obtained by curing the adhesive composition is not too high, which is preferable. Also, when the content of the polyfunctional (meth)acrylate is 15 mol% or less, the fluidity of the cured product obtained by curing the adhesive composition is in a preferable range when the cured product is used as an adhesive layer of a semiconductor processing tape. Therefore, a semiconductor processing tape using the cured product as an adhesive layer has sufficient unevenness absorption properties, and when the tape is attached to an adherend having uneven parts on the surface, it is difficult for gaps to occur between the adhesive layer and the uneven parts of the adherend, which is preferable.
[0068] The content of the (meth)acrylate monomer (B) in the pressure-sensitive adhesive composition of this embodiment is preferably 35 to 79 mass%, more preferably 40 to 73 mass%, and even more preferably 45 to 66 mass%. When the content of the (meth)acrylate monomer (B) is 35 mass% or more, the viscosity of the pressure-sensitive adhesive composition does not become too high, and excellent coatability is obtained, which is preferable. In addition, when the content of the (meth)acrylate monomer (B) is 79 mass% or less, the viscosity of the pressure-sensitive adhesive composition does not become too low, and the thickness of the coating film made of the pressure-sensitive adhesive composition is easily controlled, which is preferable.
[0069] (Chain transfer agent (C)) The chain transfer agent (C) is contained in the pressure-sensitive adhesive composition for the purpose of controlling the unevenness absorbency and gel fraction of the cured product obtained by curing the pressure-sensitive adhesive composition. As the chain transfer agent (C), it is preferable to use a thiol compound. In particular, it is preferable to use a polyfunctional thiol. The polyfunctional thiol is a compound having two or more mercapto groups in the molecule.
[0070] The polyfunctional thiol is not particularly limited, but examples thereof include 1,2-ethanedithiol, 1,4-bis(3-mercaptobutyryloxy)butane, tetraethylene glycol bis(3-mercaptopropionate), trimethylolethane tris(3-mercaptobutyrate), trimethylolpropane tris(3-mercaptobutyrate), trimethylolpropane tris(3-mercaptopropionate), pentaerythritol, Examples of the chain transfer agent (C) include pentaerythritol tetrakis(3-mercaptobutyrate), pentaerythritol tetrakis(3-mercaptopropionate), 1,3,5-tris(3-mercaptobutyloxyethyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, tris-[(3-mercaptopropionyloxy)-ethyl]-isocyanurate, and dipentaerythritol hexakis(3-mercaptopropionate). Among the above, it is preferable to use pentaerythritol tetrakis(3-mercaptobutyrate) as the chain transfer agent (C) from the viewpoint of the reactivity of the pressure-sensitive adhesive composition.
[0071] The content of the chain transfer agent (C) in the pressure-sensitive adhesive composition of this embodiment is preferably 0.5 to 8 mass%, more preferably 1 to 5 mass%, and even more preferably 3 to 4.5 mass%. When the content of the chain transfer agent (C) is 0.5 mass% or more, the fluidity of the cured product obtained by curing the pressure-sensitive adhesive composition is in a preferred range when the cured product is used as a pressure-sensitive adhesive layer of a semiconductor processing tape. Therefore, the semiconductor processing tape using the cured product as a pressure-sensitive adhesive layer has sufficient unevenness absorption properties, and is less likely to generate gaps between the uneven parts of the adherend, which is preferable. When the content is 8 mass% or less, the semiconductor processing tape using the cured product of the pressure-sensitive adhesive composition as a pressure-sensitive adhesive layer is less likely to leave adhesive residue when peeled off from the adherend, which is preferable.
[0072] (Photopolymerization initiator (D)) The photopolymerization initiator (D) is not particularly limited, but a photoradical polymerization initiator is preferred. As the photopolymerization initiator (D), for example, a carbonyl-based photopolymerization initiator, a sulfide-based photopolymerization initiator, an acylphosphine oxide-based photopolymerization initiator, a quinone-based photopolymerization initiator, a sulfochloride-based photopolymerization initiator, a thioxanthone-based photopolymerization initiator, etc. can be used. Among these photopolymerization initiators (D), it is preferable to use a carbonyl-based photopolymerization initiator and / or an acylphosphine oxide-based photopolymerization initiator from the viewpoint of the transparency of the cured product obtained by photocuring the pressure-sensitive adhesive composition. Specifically, it is more preferable to use 2,4,6-trimethylbenzoyldiphenylphosphine oxide agent and / or 1-hydroxycyclohexyl-phenyl ketone.
[0073] The content of the photopolymerization initiator (D) in the pressure-sensitive adhesive composition of this embodiment is preferably 0.01 to 5 mass%, more preferably 0.05 to 3 mass%, and even more preferably 0.1 to 2 mass%. When the content of the photopolymerization initiator (D) is 0.01 mass% or more, the photocuring of the pressure-sensitive adhesive composition proceeds sufficiently. When the content of the photopolymerization initiator (D) is 5 mass% or less, the amount of low molecular weight components does not become too large during photocuring of the pressure-sensitive adhesive composition. Therefore, when a semiconductor processing tape using a cured product of the pressure-sensitive adhesive composition as a pressure-sensitive adhesive layer is peeled off from an adherend, adhesive residue is unlikely to be left, which is preferable.
[0074] (Fatty acid ester (E)) The pressure-sensitive adhesive composition of the present embodiment contains a polyurethane (A), a (meth)acrylate monomer (B), a chain transfer agent (C), and a photopolymerization initiator (D), and may further contain a fatty acid ester (E) as necessary. The fatty acid ester (E) is contained in the adhesive composition for the purposes of controlling the adhesive strength in a semiconductor processing tape that uses a cured product of the adhesive composition as an adhesive layer, and improving the lamination properties (wettability) and bubble removal properties (ease of removal of air bubbles trapped when the semiconductor processing tape is bonded to the adherend) of the adhesive layer.
[0075] As the fatty acid ester (E), an ester of a fatty acid and an alkyl alcohol can be used. From the viewpoint of compatibility with other components, it is preferable to use a fatty acid ester selected from the group consisting of an ester of a fatty acid having 8 to 18 carbon atoms and a monofunctional alcohol having a branched hydrocarbon group having 3 to 18 carbon atoms, and an ester of an unsaturated fatty acid having 14 to 18 carbon atoms and a di- to tetrafunctional alcohol.
[0076] Examples of esters of fatty acids having 8 to 18 carbon atoms and monofunctional alcohols having a branched hydrocarbon group having 3 to 18 carbon atoms include isostearyl laurate, isopropyl myristate, isocetyl myristate, octyldodecyl myristate, isopropyl palmitate, isostearyl palmitate, isocetyl stearate, 2-ethylhexyl stearate, octyldodecyl oleate, diisostearyl adipate, diisocetyl sebacate, trioleyl trimellitate, and triisocetyl trimellitate. Among these, it is preferable to use isopropyl myristate, isopropyl palmitate, and 2-ethylhexyl stearate, and it is particularly preferable to use isopropyl myristate and / or 2-ethylhexyl stearate.
[0077] Examples of esters of unsaturated fatty acids having 14 to 18 carbon atoms and di- to tetrafunctional alcohols include esters of unsaturated fatty acids such as myristoleic acid, oleic acid, linoleic acid, linolenic acid, isopalmitic acid, and isostearic acid with alcohols such as ethylene glycol, propylene glycol, glycerin, trimethylolpropane, pentaerythritol, and sorbitan.
[0078] The content of the fatty acid ester (E) in the pressure-sensitive adhesive composition of the present embodiment is preferably from 3 to 18 mass %, more preferably from 5 to 15 mass %. When the content of fatty acid ester (E) is 3% by mass or more, the adhesive strength of the semiconductor processing tape using the cured product of the adhesive composition as the adhesive layer falls within a preferred range, and the lamination property and bubble releasing property of the adhesive layer become good. When the content of fatty acid ester (E) is 18% by mass or less, adhesive residue containing fatty acid ester (E) is unlikely to be left when the semiconductor processing tape using the cured product of the adhesive composition as the adhesive layer is peeled off from the adherend, which is preferable.
[0079] (solvent) The pressure-sensitive adhesive composition of the present embodiment may contain a solvent, but is more preferably a solvent-free composition that is substantially free of solvent. When the pressure-sensitive adhesive composition of the present embodiment contains a solvent, the solvent can be used, for example, as a leveling agent and / or a softening agent.
[0080] When the adhesive composition of the present embodiment is solvent-free, the step of heating and drying the solvent can be omitted when forming the adhesive layer of the semiconductor processing tape using the adhesive composition, and therefore excellent productivity can be obtained. In particular, when the adhesive composition of the present embodiment is used to manufacture a semiconductor processing tape having an adhesive layer with a thickness of more than 50 μm, the productivity improvement effect of omitting the step of heating and drying the solvent is remarkable, so that it is preferable that the adhesive composition is solvent-free.
[0081] In the present invention, the pressure-sensitive adhesive composition being "substantially free of solvent" means that the solvent content in the pressure-sensitive adhesive composition is 0 to 1 mass %, preferably 0 to 0.5 mass %, and more preferably 0 to 0.1 mass %.
[0082] (others) The pressure-sensitive adhesive composition of the present embodiment may contain other additives as necessary within the range that does not impair the effects of the present invention. Examples of the additives include plasticizers, surface lubricants, antioxidants, antiaging agents, light stabilizers, ultraviolet absorbers, polymerization inhibitors, benzotriazole-based light stabilizers, phosphate ester-based and other flame retardants, dyes, etc.
[0083] <Method of producing pressure-sensitive adhesive composition> Next, the method for producing the adhesive composition of this embodiment will be described in detail with examples. Hereinafter, of the components contained in the adhesive composition of this embodiment, a preferred synthesis method for the polyurethane (A) will be described with examples. Of the components contained in the adhesive composition of this embodiment, each component other than the polyurethane (A), such as the (meth)acrylate monomer (B), the chain transfer agent (C), the photopolymerization initiator (D), and the fatty acid ester (E), can be easily purchased as a commercially available product. In addition, the synthesis method differs depending on the type of compound used as each component. Therefore, the description of the synthesis method will be omitted.
[0084] <Method of synthesizing polyurethane (A)> Hereinafter, an example of a preferred synthesis method for the polyurethane (A) contained in the pressure-sensitive adhesive composition of the present embodiment will be described. Note that the synthesis method for the polyurethane (A) is not limited to the synthesis method shown below, and can be appropriately changed depending on the conditions of the raw materials and equipment used in the synthesis.
[0085] In the synthesis method of polyurethane (A) shown below, the reaction between hydroxyl groups and isocyanato groups is carried out in the presence of an organic solvent inactive to isocyanato groups in any step using a urethanization catalyst. Examples of the urethanization catalyst include dibutyltin dilaurate, dibutyltin diethylhexoate, and dioctyltin dilaurate. In any step, the reaction between hydroxyl groups and isocyanato groups is preferably carried out continuously for 1 to 5 hours at 30 to 100°C. The amount of the urethanization catalyst used is preferably 50 to 500 ppm by mass based on the total mass of the reactants (raw materials).
[0086] To synthesize polyurethane (A), first, polyoxyalkylene polyol and polyisocyanate are charged in a ratio such that the amount of isocyanato groups (based on the number of molecules, the same applies below) is greater than the amount of hydroxyl groups (based on the number of molecules, the same applies below). Then, the polyoxyalkylene polyol and polyisocyanate are reacted to synthesize polyurethane having isocyanato groups at the ends as a precursor of polyurethane (A). Specific examples of polyoxyalkylene polyol and polyisocyanate used as raw materials are as exemplified in the section on polyurethane (A).
[0087] At this time, the molecular weight (degree of polymerization) of the polyurethane having isocyanato groups at its terminals can be adjusted by adjusting the ratio of the amount of isocyanato groups to the amount of hydroxyl groups contained in the raw material. Specifically, the smaller the excess amount of isocyanato groups relative to the amount of hydroxyl groups, the higher the molecular weight of the polyurethane having isocyanato groups at its terminals. Also, the greater the excess amount of isocyanato groups relative to the amount of hydroxyl groups, the lower the molecular weight of the polyurethane having isocyanato groups at its terminals. In this embodiment, the weight average molecular weight of the target polyurethane (A) is adjusted by adjusting the molecular weight of the polyurethane having isocyanato groups at its terminals.
[0088] Next, the polyurethane having an isocyanato group at the end is reacted with a compound having a hydroxy group and a (meth)acryloyl group to produce a polyurethane (A) containing a polyurethane (a1). The polyurethane (a1) has a skeleton containing a structure derived from a polyoxyalkylene polyol and a structure derived from a polyisocyanate, and has a plurality of (meth)acryloyl groups at the ends. The (meth)acryloyl groups at the ends of the produced polyurethane (A) are preferably part of a (meth)acryloyloxy group.
[0089] The compound having a hydroxy group and a (meth)acryloyl group is not particularly limited, but includes hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; monools having a (meth)acryloyl group derived from various polyols such as 1,3-butanediol mono(meth)acrylate, 1,4-butanediol mono(meth)acrylate, 1,6-hexanediol mono(meth)acrylate, and 3-methylpentanediol mono(meth)acrylate. These compounds having a hydroxy group and a (meth)acryloyl group may be used alone or in combination of two or more. Among these compounds having a hydroxy group and a (meth)acryloyl group, it is preferable to use 2-hydroxyethyl (meth)acrylate in terms of reactivity with the isocyanato group of polyurethane having an isocyanato group at the end and photocurability of the adhesive composition.
[0090] Alternatively, the polyurethane (A) may be produced by reacting a compound having a hydroxy group and a (meth)acryloyl group with an alkyl alcohol having no (meth)acryloyl group and one hydroxy group, together with a polyurethane having an isocyanato group at its terminal. The alkyl alcohol is not particularly limited as long as it does not have a (meth)acryloyl group and has one hydroxyl group, and may be a linear, branched, or alicyclic alkyl alcohol. The alkyl alcohol may be used alone or in combination of two or more kinds.
[0091] By reacting a compound having a hydroxy group and a (meth)acryloyl group, an alkyl alcohol having no (meth)acryloyl groups but one hydroxy group, and a polyurethane having an isocyanato group at its terminal to produce polyurethane (A), it is possible to adjust the amount of (meth)acryloyl groups introduced into the polyurethane having an isocyanato group at its terminal.
[0092] More specifically, according to the above reaction, polyurethane (A) is produced that includes a plurality of types of polyurethanes having different amounts of (meth)acryloyl groups introduced at the terminals. The plurality of types of polyurethanes includes polyurethane (a1) having (meth)acryloyl groups at a plurality of terminals. Furthermore, the plurality of types of polyurethanes includes not only polyurethane (a1) but also polyurethanes having at least a portion of the plurality of terminals that have a structure derived from the above alkyl alcohol. Therefore, the plurality of types of polyurethanes produced includes polyurethanes having at least a portion of the plurality of terminals that do not have a (meth)acryloyl group. Furthermore, the plurality of types of polyurethanes produced may also include polyurethane (a2) having a (meth)acryloyl group at only one terminal.
[0093] <Another example of the synthesis method of polyurethane (A)> Next, another preferred example of the synthesis method for the polyurethane (A) will be described. In the synthesis method of polyurethane (A) shown below, as in the above synthesis method example, the reaction between hydroxyl groups and isocyanato groups is carried out in the presence of an organic solvent inactive to isocyanato groups using a urethanization catalyst in each step. Examples of the urethanization catalyst include dibutyltin dilaurate, dibutyltin diethylhexoate, and dioctyltin dilaurate. In addition, the reaction between hydroxyl groups and isocyanato groups is preferably carried out continuously for 1 to 5 hours at 30 to 100°C in each step. The amount of the urethanization catalyst used is preferably 50 to 500 ppm by mass based on the total mass of the reactants (raw materials).
[0094] When polyurethane (A) is synthesized using this synthesis method, unlike the above-mentioned example synthesis method, a polyurethane having a terminal hydroxy group is synthesized as a precursor of polyurethane (A). Specifically, first, polyoxyalkylene polyol and polyisocyanate are charged in a ratio such that the amount of hydroxyl groups (based on the number of molecules, the same applies below) is greater than the amount of isocyanato groups (based on the number of molecules, the same applies below).Then, the polyoxyalkylene polyol and the polyisocyanate are reacted to synthesize a polyurethane having a hydroxyl group at its terminal as a precursor of polyurethane (A).
[0095] At this time, the molecular weight (degree of polymerization) of the polyurethane having hydroxyl groups at its terminals can be adjusted by adjusting the ratio of the amount of hydroxyl groups to the amount of isocyanato groups contained in the raw material. Specifically, the smaller the excess amount of hydroxyl groups relative to the amount of isocyanato groups, the higher the molecular weight of the polyurethane having hydroxyl groups at its terminals. Also, the greater the excess amount of hydroxyl groups relative to the amount of isocyanato groups, the lower the molecular weight of the polyurethane having hydroxyl groups at its terminals. In this embodiment, the mass average molecular weight of the target polyurethane (A) is adjusted by adjusting the molecular weight of the polyurethane having hydroxyl groups at its terminals.
[0096] Next, the polyurethane having a hydroxyl group at the end is reacted with a compound having an isocyanato group and a (meth)acryloyl group to produce a polyurethane (A) having a skeleton including a structure derived from a polyoxyalkylene polyol and a structure derived from a polyisocyanate, and including a polyurethane (a1) having (meth)acryloyl groups at a plurality of ends. The (meth)acryloyl groups at the ends of the produced polyurethane (A) are preferably part of a (meth)acryloyloxy group.
[0097] The compound having an isocyanato group and a (meth)acryloyl group is not particularly limited, and examples thereof include 2-(meth)acryloyloxyethyl isocyanate, 2-(meth)acryloyloxypropyl isocyanate, and 1,1-bis(acryloyloxymethyl)ethyl isocyanate. In addition, examples of commercially available products of the compound having an isocyanato group and a (meth)acryloyl group include Karenz MOI (registered trademark) and Karenz AOI (registered trademark) manufactured by Showa Denko K.K. These compounds having an isocyanato group and a (meth)acryloyl group may be used alone or in combination of two or more kinds. Among these compounds having an isocyanato group and a (meth)acryloyl group, it is preferable to use 2-(meth)acryloyloxyethyl isocyanate in terms of reactivity with the hydroxy group of polyurethane having a hydroxy group at the end and photocurability of the pressure-sensitive adhesive composition.
[0098] Alternatively, the polyurethane (A) may be produced by reacting a compound having an isocyanato group and a (meth)acryloyl group with an alkyl isocyanate having no (meth)acryloyl group and one isocyanato group, together with a polyurethane having a hydroxyl group at its terminal. The alkyl isocyanate is not particularly limited as long as it does not have a (meth)acryloyl group and has one isocyanato group, and may be a linear, branched, or alicyclic alkyl isocyanate. The alkyl isocyanate may be used alone or in combination of two or more kinds.
[0099] The amount of (meth)acryloyl groups introduced into the polyurethane having hydroxyl groups at its terminals can be adjusted by reacting a compound having an isocyanato group and a (meth)acryloyl group, an alkyl isocyanate having one isocyanato group but no (meth)acryloyl group, and a polyurethane having hydroxyl groups at its terminals to produce polyurethane (A).
[0100] More specifically, according to the above reaction, polyurethane (A) is produced that includes a plurality of types of polyurethanes having different amounts of (meth)acryloyl groups introduced at the terminals. The plurality of types of polyurethanes includes polyurethane (a1) having (meth)acryloyl groups at a plurality of terminals. Furthermore, the plurality of types of polyurethanes includes not only polyurethane (a1) but also polyurethanes having at least a portion of the plurality of terminals that have a structure derived from the alkyl isocyanate. Therefore, the plurality of types of polyurethanes produced includes polyurethanes having at least a portion of the plurality of terminals that do not have a (meth)acryloyl group. Furthermore, the plurality of types of polyurethanes produced may also include polyurethane (a2) having a (meth)acryloyl group at only one terminal.
[0101] <Method of mixing components contained in pressure-sensitive adhesive composition> The pressure-sensitive adhesive composition of the present embodiment can be produced by a method of mixing the polyurethane (A) obtained by the above-mentioned synthesis method, a (meth)acrylate monomer (B), a chain transfer agent (C), a photopolymerization initiator (D), and, if necessary, a fatty acid ester (E) and other additives. The method for mixing the components contained in the pressure-sensitive adhesive composition of the present embodiment is not particularly limited, and can be carried out using, for example, a stirring device equipped with stirring blades such as a homodisper or a paddle blade.
[0102] <Method of manufacturing semiconductor processing tape> Next, a method for producing the semiconductor processing tape of this embodiment will be described. The method for producing the semiconductor processing tape of this embodiment is not particularly limited, and the tape can be produced using a known method. For example, fine particles of polypyrrole and / or polypyrrole derivative are dispersed in a hydrophilic solvent using a polymer dispersant and / or a dopant, and further mixed with a water-soluble or water-dispersible binder resin to prepare a resin composition; this resin composition is applied onto a substrate body such as a polymer film, and the solvent is then dried and removed to obtain a substrate having an antistatic layer. Next, a pressure-sensitive adhesive composition is applied onto the antistatic layer of the substrate, and a transparent separator film is laminated to form a laminate. Thereafter, the pressure-sensitive adhesive composition is irradiated with ultraviolet light through the separator to photocure the pressure-sensitive adhesive composition. This results in a semiconductor processing tape having a pressure-sensitive adhesive layer, which is a cured product of the pressure-sensitive adhesive composition, formed on a substrate having an antistatic layer.
[0103] The method of applying the adhesive composition to the substrate is not particularly limited and can be appropriately selected. For example, the method of applying the adhesive composition to the substrate can be a method using various coaters such as a gravure roll coater, a reverse roll coater, a kiss roll coater, a dip roll coater, a bar coater, a knife coater, a spray coater, a comma coater, a direct coater, or a screen printing method.
[0104] Examples of light sources for photocuring the pressure-sensitive adhesive composition include black lights, low-pressure mercury lamps, high-pressure mercury lamps, extra-high-pressure mercury lamps, metal halide lamps, and xenon lamps. The light irradiation intensity is preferably set to a level that allows the pressure-sensitive adhesive composition to be sufficiently cured and the gel fraction of the cured product to fall within a range of 50 to 65% by mass, for example, 50 to 3,000 mW / cm. 2 It is preferable that the light irradiation intensity is low. If the light irradiation intensity is low, it takes a long time to cure, resulting in a decrease in productivity.
[0105] In this embodiment, the pressure-sensitive adhesive composition is irradiated with ultraviolet light through a transparent separator, but if the substrate is transparent, ultraviolet light may be irradiated from the substrate side, or an opaque separator may be used.
[0106] <Uses and required performance of tape for semiconductor processing> The semiconductor processing tape of this embodiment can be used, for example, in applications where it is attached to an adherend having an uneven surface and then peeled off. Specifically, it can be used suitably as a backgrind tape for semiconductor wafer processing, which is attached to the surface of a semiconductor wafer on which bumps are formed to protect the surface of the semiconductor wafer and is peeled off after a predetermined wafer processing step.
[0107] When the semiconductor processing tape of this embodiment is used to protect the surface of a semiconductor wafer having bumps formed on its surface, the peel strength (adhesive strength) of the semiconductor processing tape must be such that the semiconductor processing tape is firmly fixed to the semiconductor wafer, for example, in the back grinding step in the semiconductor device processing process. On the other hand, the peel strength of the semiconductor processing tape must be strong enough not to damage the components of the semiconductor device when the semiconductor processing tape is peeled off from the semiconductor wafer after a specified processing step.
[0108] From these viewpoints, the peel strength of the semiconductor processing tape used for the above-mentioned applications is preferably 10 to 300 gf / 25 mm, more preferably 15 to 200 gf / 25 mm, and even more preferably 20 to 150 gf / 25 mm, when the peel speed is 0.3 m / min. and the thickness of the adhesive layer is 50 to 200 μm. When the thickness of the adhesive layer is 200 to 500 μm, the peel strength is preferably 50 to 500 gf / 25 mm, more preferably 60 to 400 gf / 25 mm, and even more preferably 70 to 300 gf / 25 mm. A specific method for measuring the peel strength of the semiconductor processing tape will be described later in the examples.
[0109] The semiconductor processing tape of this embodiment has an adhesive layer, which is a cured product of the adhesive composition of this embodiment, on one side of the substrate on which an antistatic layer is formed. Therefore, the semiconductor processing tape of this embodiment has sufficient adhesive strength, is unlikely to leave adhesive residue on the adherend due to the adhesive layer being transferred to the adherend after the semiconductor processing tape is peeled off, and is excellent in unevenness absorption and antistatic performance. Therefore, the semiconductor processing tape of this embodiment is suitable for applications in which it is attached to an adherend having uneven parts on the surface and then peeled off.
[0110] The semiconductor processing tape of this embodiment can be suitably used as a semiconductor processing tape that is applied during the back-grinding process of a semiconductor wafer having uneven portions made of bumps on its surface, and is peeled off after the back-grinding process. In this case, the semiconductor processing tape of this embodiment fixes the semiconductor wafer with sufficient adhesive strength. Moreover, since the semiconductor processing tape has sufficient unevenness absorption properties, gaps are unlikely to occur between the semiconductor processing tape applied to the semiconductor wafer and the periphery of the bumps. Therefore, it is possible to prevent the water used in the back-grinding process from penetrating the gap between the semiconductor processing tape and the periphery of the bumps, thereby preventing the semiconductor wafer from being contaminated. In addition, since the semiconductor processing tape of this embodiment has sufficient antistatic properties, peeling electrification can be suppressed when the semiconductor processing tape applied to the semiconductor wafer is peeled off after the back-grinding process. Furthermore, it is preferable that adhesive residue is unlikely to occur around the bumps of the semiconductor wafer from which the semiconductor processing tape has been peeled off after the back-grinding process.
[0111] The semiconductor processing tape of this embodiment can have a single-layer structure in which the adhesive layer is a cured product of the adhesive composition. In this case, the adhesive layer can be formed by only performing a process of forming one layer. Therefore, the semiconductor processing tape of this embodiment can be easily manufactured with fewer manufacturing processes compared to the case of forming a semiconductor processing tape provided with a layer having unevenness absorption properties and a layer having adhesive power, for example. EXAMPLES
[0112] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples.
[0113] (Production Example 1) <Production of sheet-like substrate 1 having antistatic layer> A water dispersion was prepared by mixing 9.4 parts by mass of polypyrrole dispersion (PPY-12, solid content 8%, manufactured by Marubishi Petrochemical Co., Ltd.), 5.0 parts by mass of polyester binder (BI-12, solid content 30%, manufactured by Marubishi Petrochemical Co., Ltd.), 2.6 parts by mass of melamine crosslinking agent (CL-12, solid content 25%, manufactured by Marubishi Petrochemical Co., Ltd.), 0.05 parts by mass of polyoxyethylene lauryl ether, and 830.0 parts by mass of water. Next, the resin composition was applied to one side of a 50 μm-thick PET film (manufactured by Toyobo Co., Ltd., product name: Ester (trademark) film E5100) as the substrate body using a gravure coater so that the film thickness after heat curing was 1.0 μm. Next, the substrate was cured at 130 ° C. for 1 minute to obtain a sheet-like substrate 1. The electrical resistance of the substrate 1 measured with a low resistivity meter (Loresta-AX, manufactured by Mitsubishi Chemical Analytech Co., Ltd.) was 8 × 10 5 The value was Ω·cm.
[0114] (Comparative Manufacturing Example 1) <Production of sheet-like substrate 2 having antistatic layer> 93.0 parts by mass of polythiophene (H.C. Starck Clevios (trademark) P, solid content 1%), 6.8 parts by mass of polyester resin (Toyobo Vylonal (trademark) MD-1930, solid content 31%), 2.4 parts by mass of melamine-based crosslinking agent (Marubishi Yuka Kogyo CL-12, solid content 25%), 0.05 parts by mass of polyoxyethylene lauryl ether, and 900.0 parts by mass of water were mixed to prepare an aqueous dispersion. Next, the resin composition was applied to one side of a 50 μm-thick PET film (Toyobo, product name: Ester (trademark) film E5100) as the substrate body using a gravure coater so that the film thickness after heat curing was 1.0 μm. Next, the substrate was cured at 130° C. for 1 minute to obtain a sheet-like substrate 2. The electrical resistance of the substrate 2 measured with a low resistivity meter (Mitsubishi Chemical Analytech Co., Ltd. Loresta-AX) was 4×10 5The value was Ω·cm.
[0115] (Synthesis Example 1) <Synthesis of Polyurethane (A-1)> A reactor equipped with a thermometer, a stirrer, a dropping funnel, and a cooling tube with a drying tube was charged with 0.55 kg (2.1 mol) of a hydrogenated product of diphenylmethane diisocyanate (Desmodur W, manufactured by Sumika Covestro Urethane Co., Ltd.), 4.01 kg (2.0 mol) of polypropylene glycol having a hydroxyl group at its terminal and a hydroxyl value of 56 mg KOH / g (Actocol D-2000, manufactured by Mitsui Chemicals, number average molecular weight 2000), and 0.8 g of a urethanization catalyst dioctyltin (Neostan U-810, manufactured by Nitto Kasei Co., Ltd.).
[0116] The reactor was then heated to 60°C and reacted for 4 hours to obtain a polyurethane having isocyanato groups at both ends as a precursor of polyurethane (A). 23.22g (0.2mol) of 2-hydroxyethyl acrylate was then added to the reactor, heated to 70°C and reacted for 2 hours to obtain 4.58kg of polyurethane (A-1) having a mass average molecular weight of 67,000.
[0117] The obtained polyurethane (A-1) was analyzed by infrared absorption spectroscopy (IR). As a result, no peaks derived from isocyanato groups were observed. Therefore, it was confirmed that polyurethane (A-1) was polyurethane (a1) in which acryloyloxy groups were introduced at all ends.
[0118] (Synthesis Example 2) <Synthesis of Polyurethane (A-2)> A polyurethane (A-2) having a mass average molecular weight of 66,000 was obtained in the same manner as in the synthesis of polyurethane (A-1), except that 2.1 mol of isophorone diisocyanate (Desmodur I, manufactured by Sumika Covestro Urethane Co., Ltd.) was used instead of the hydrogenated product of diphenylmethane diisocyanate.
[0119] The obtained polyurethane (A-2) was analyzed by infrared absorption spectroscopy (IR). As a result, no peaks derived from isocyanato groups were observed. Therefore, it was confirmed that polyurethane (A-2) was polyurethane (a1) in which acryloyloxy groups were introduced at all ends.
[0120] (Formulation examples 1 to 3, Comparative combination examples 1 to 4) <Preparation of Pressure-Sensitive Adhesive Composition> The polyurethane (A) obtained by the above synthesis method, the (meth)acrylate monomer (B), the chain transfer agent (C), the photopolymerization initiator (D), and the fatty acid ester (E) shown in Table 1 were blended in the ratios shown in Table 1 and mixed at 25°C using a disper to obtain pressure-sensitive adhesive compositions c1 to c7 of Blending Examples 1 to 3 and Comparative Blending Examples 1 to 4.
[0121] [Table 1]
[0122] The following symbols in Table 1 represent the compounds shown below. 2EHA: 2-Ethylhexyl acrylate (manufactured by Toagosei Co., Ltd.) BUA: n-butyl acrylate (manufactured by Toagosei Co., Ltd.) ACMO: Acryloylmorpholine (manufactured by Shin-Nakamura Chemical Co., Ltd.) TMPTA: Trimethylolpropane triacrylate (manufactured by Toagosei Co., Ltd.)
[0123] PE1: Pentaerythritol tetrakis(3-mercaptobutyrate) (Showa Denko K.K.) NR1: 1,3,5-tris(3-mercaptobutyloxyethyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione (Showa Denko K.K.) TPO (Omnirad TPO H): 2,4,6-trimethylbenzoyldiphenylphosphine oxide (manufactured by IGM Resins BV) 184 (Omnirad 184): 1-hydroxycyclohexyl-phenyl ketone (IGM Resins BV) Exepar IPM: Isopropyl myristate (Kao Corporation) Exepar EH-S: 2-ethylhexyl stearate (Kao Corporation)
[0124] Example 1 The pressure-sensitive adhesive composition c1 of Formulation Example 1 in Table 1 was applied to the antistatic layer side of the substrate 1 using an applicator so as to give a thickness of 150 μm after curing. Next, a 75 μm thick silicone-based ultra-light release PET film (product name: E7006, manufactured by Toyobo Co., Ltd.) was attached as a separator to the surface coated with the pressure-sensitive adhesive composition using a rubber roller. Thereafter, the adhesive composition was irradiated through a separator with an ultraviolet ray irradiator (3 kW UV irradiator, high pressure mercury lamp, manufactured by iGraphics Co., Ltd.) at an irradiation distance of 25 cm, a lamp moving speed of 1.0 m / min, and an irradiation dose of 1000 mJ / cm. 2 The adhesive composition was photocured by irradiating ultraviolet light under the conditions of: 1. This resulted in a semiconductor processing tape of Example 1 in which an adhesive layer, which was a cured product of the adhesive composition, and a separator were laminated on a substrate.
[0125] (Examples 2 to 3 and Comparative Examples 1 to 6) Semiconductor processing tapes were produced in the same manner as in Example 1, except that the substrates and adhesive compositions c2 to c7 shown in Table 2 were used and the adhesive layer had a thickness shown in Table 2. As a result, the semiconductor processing tapes of Examples 2 to 3 and Comparative Examples 1 to 6 were obtained.
[0126] Next, the items shown below were evaluated for the tapes for semiconductor processing of Examples 1 to 3 and Comparative Examples 1 to 4. The results are shown in Table 2. <Measurement of surface resistivity> The semiconductor processing tape was cut into a size of 120 mm long and 120 mm wide, and left for 3 hours in an environment of 23°C temperature and 50% RH relative humidity to condition the humidity. After that, the release PET film was peeled off to expose the adhesive layer, and the surface resistivity of the adhesive layer side was measured using a high resistivity meter (Mitsubishi Chemical Analytec Co., Ltd., Hiresta-UX) under the condition of an applied voltage of 100V x 60 seconds. Then, it was evaluated according to the following criteria. The smaller the surface resistivity, the less likely peeling static electricity occurs when the semiconductor processing tape attached to the semiconductor wafer is peeled off, and it can be said that the semiconductor processing tape has excellent antistatic performance.
[0127] Evaluation criteria ◎: Surface resistivity is 1×10 11 Less than Ω / □ ○: Surface resistivity is 1×10 11 Ω / □ or more and 1×10 12 Less than Ω / □ △: Surface resistivity is 1×10 12 Ω / □ or more and 1×10 13 Less than Ω / □ ×: Surface resistivity is 1×10 13 Ω / □ or more
[0128] <Peeling force (peeling strength)> The semiconductor processing tape was cut into a size of 25 mm long and 150 mm wide, and the separator was peeled off to expose the adhesive layer. The entire surface of the exposed adhesive layer was then laminated onto a glass plate, and a rubber roller (diameter: 85 mm, width: 50 mm) with a mass of 2 kg (load of 19.6 N) was rolled back and forth once to obtain a measurement sample. The obtained measurement sample was left for 30 minutes in an environment of a temperature of 23°C and a relative humidity of 50% RH. Then, a tensile test was performed in the 180° direction at a peeling speed of 0.3 m / min. in accordance with JIS K 6854-2 to measure the peel strength (gf / 25 mm) against the glass plate.
[0129] <Irregularity absorption> The semiconductor processing tape was cut into a size of 25 mm long and 50 mm wide, and the separator was peeled off to expose the adhesive layer. Then, the surface of the exposed adhesive layer was placed facing the bumps of a bumped wafer (WALTS-TEG FC150SCJY LF(PI), bump height: 75 μm, bump size: diameter 90 μm, manufactured by Waltz Corporation). Then, a rubber roller (diameter: 85 mm, width: 50 mm) with a mass of 2 kg (load 19.6 N) was reciprocated three times at a speed of 10 mm / sec on the substrate of the semiconductor processing tape to bond the semiconductor processing tape and the bumped wafer.
[0130] The bumped wafer bonded to the semiconductor processing tape was observed from the substrate side of the semiconductor processing tape with a digital optical microscope (RH-2000, manufactured by Keihin Hirox Co., Ltd.), and the unevenness absorbency of the bumps was evaluated according to the following criteria. "standard" ◯: There is no gap between the adhesive layer of the semiconductor processing tape and the periphery of the bumps on the bumped wafer. ×: There is a gap between the adhesive layer of the semiconductor processing tape and the periphery of the bumps of the bumped wafer.
[0131] <Contamination caused by glue residue> The semiconductor processing tape was cut into a size of 25 mm long and 50 mm wide, and the separator was peeled off to expose the adhesive layer. Then, the surface of the exposed adhesive layer was placed facing the bumps of a bumped wafer (WALTS-TEG FC150SCJY LF(PI), manufactured by Waltz Corporation, bump height: 75 μm, bump size: diameter 90 μm). Then, a rubber roller (diameter: 85 mm, width: 50 mm) with a mass of 2 kg (load 19.6 N) was reciprocated three times at a speed of 10 mm / sec on the substrate of the semiconductor processing tape to bond the semiconductor processing tape and the bumped wafer.
[0132] The bumped wafer attached to the semiconductor processing tape was left at 23°C for 24 hours, and then the semiconductor processing tape was peeled off by hand at a speed of about 2 m / min. The surface of the bumped wafer was then observed with a digital optical microscope (RH-2000, manufactured by Hirox Co., Ltd.) and the presence or absence of contamination due to adhesive residue was evaluated according to the following criteria. Note that "adhesive residue" means that the adhesive layer itself remains attached to the wafer surface, causing the wafer surface to be sticky. "standard" ◯: No contamination due to adhesive residue around the bumps. ×: Contamination due to adhesive residue around the bumps.
[0133] <Measurement of gel fraction> The adhesive composition was applied using an applicator onto a 75 μm-thick release PET film (manufactured by Higashiyama Film Co., Ltd., product name: Clean Sepa (trademark) HY-S10-2) so that the thickness after curing would be 150 μm. In Comparative Example 4, the thickness after curing was adjusted to 30 μm. Next, the surface to which the adhesive composition was applied was covered with a 75 μm-thick silicone-based ultra-light release PET film (manufactured by Toyobo Co., Ltd., product name: E7006).
[0134] Next, an ultraviolet irradiation device (3kW UV irradiation device, high-pressure mercury lamp, manufactured by Eye Graphics Co., Ltd.) was used, and the irradiation distance was 25cm, the lamp movement speed was 1.0m / min, and the irradiation dose was 1000mJ / cm. 2 The pressure-sensitive adhesive composition was cured by irradiation with ultraviolet light through the ultra-easy release PET film under the conditions above to obtain a cured product (pressure-sensitive adhesive layer).
[0135] Next, the cured product (adhesive layer) was cut into a size of about 1 g, and the PET films on both sides were peeled off to prepare a measurement sample, and its mass was measured. Next, the measurement sample was immersed in 50 ml of toluene and left at room temperature for 72 hours. After that, the measurement sample was taken out of the toluene, dried at 80°C for 5 hours, and its mass was measured again. Then, the gel fraction was measured based on the following formula. Gel fraction (%) = [A / B] x 100 A: Mass of the measurement sample after immersion in toluene (excluding the mass of toluene) B: Mass of the measurement sample before immersion in toluene
[0136] [Table 2]
[0137] As shown in Table 2, the semiconductor processing tapes of Examples 1 to 3 were shown to have low surface resistivity and excellent antistatic performance. In addition, they had high peeling strength (adhesive strength), excellent irregularity absorption, and did not cause contamination due to adhesive residue when peeled off from a wafer with bumps. In contrast, Comparative Example 1, in which the substrate 2 not containing a polypyrrole compound was used in the antistatic layer, showed high surface resistivity and poor antistatic performance. Comparative Examples 2, 3, and 6, in which the chain transfer agent (C) was not used in the adhesive composition, were unable to control the gel fraction of the adhesive layer within an appropriate range, resulting in poor peeling force, unevenness absorbency, or adhesive residue. Comparative Example 4, in which the adhesive layer was thin, did not provide sufficient unevenness absorbency. Comparative Example 5 used adhesive composition c6, which did not use chain transfer agent (C) and contained an increased amount of photopolymerization initiator (D) compared to adhesive composition c1. As a result, the gel fraction was equivalent to that of Example 1, but the unevenness absorbency was insufficient, and contamination due to adhesive residue also occurred. [Industrial Applicability]
[0138] According to the present invention, there is provided a semiconductor processing tape that has sufficient unevenness absorption, antistatic performance, and adhesive strength, is unlikely to leave adhesive residue, and can be manufactured with fewer manufacturing steps. The semiconductor processing tape can be preferably used in the semiconductor wafer processing step to protect the surface of the semiconductor wafer and to peel off after the processing step. In particular, it is suitable as a backgrind tape used to protect the surface during the backgrinding step of an adherend having uneven parts on its surface, such as a semiconductor wafer with bumps formed on its surface.
Claims
1. A sheet-like substrate having a substrate body and an antistatic layer provided on at least one surface of the substrate body; a pressure-sensitive adhesive layer formed on the antistatic layer; A semiconductor processing tape having the antistatic layer contains a polypyrrole compound, The pressure-sensitive adhesive layer is a cured product of a pressure-sensitive adhesive composition, The thickness of the pressure-sensitive adhesive layer is 50 to 500 μm, The pressure-sensitive adhesive composition includes a polyurethane (A), a (meth)acrylate monomer (B), a chain transfer agent (C), and a photopolymerization initiator (D), The polyurethane (A) contains polyurethane (a1), the polyurethane (a1) has a skeleton containing a structure derived from a polyoxyalkylene polyol and a structure derived from a polyisocyanate, and has (meth)acryloyl groups at a plurality of terminals; A tape for semiconductor processing, characterized in that the (meth)acrylate monomer (B) contains a monofunctional (meth)acrylate and a polyfunctional (meth)acrylate.
2. 2. The semiconductor processing tape according to claim 1, wherein the pressure-sensitive adhesive layer has a single layer structure.
3. 3. The semiconductor processing tape according to claim 1, wherein the chain transfer agent (C) is a polyfunctional thiol.
4. The semiconductor processing tape according to any one of claims 1 to 3, wherein the pressure-sensitive adhesive layer has a gel fraction of 50 to 65 mass %.
5. The surface resistivity of the pressure-sensitive adhesive layer is 1×10 12 The semiconductor processing tape according to any one of claims 1 to 4, having a resistivity of less than Ω / □.
6. The semiconductor processing tape according to any one of claims 1 to 5, wherein the (meth)acrylate monomer (B) contains 85 to 99 mol% of the monofunctional (meth)acrylate and 1 to 15 mol% of the polyfunctional (meth)acrylate.
7. The pressure-sensitive adhesive composition, 20 to 50% by mass of the polyurethane (A), 35 to 79% by mass of the (meth)acrylate monomer (B), 0.5 to 8% by mass of the chain transfer agent (C), The semiconductor processing tape according to any one of claims 1 to 6, comprising 0.01 to 5 mass % of the photopolymerization initiator (D).
8. The tape for semiconductor processing according to any one of claims 1 to 7, wherein the pressure-sensitive adhesive composition further contains a fatty acid ester (E).
Citation Information
Patent Citations
Adhesive sheet for electronic parts
JP2009120820A
Adhesive composition
JP2018002787A
Adhesive film for semiconductor wafer processing
JP2018006540A
Adhesive tape for work processing
WO2016175112A1
Adhesive tape for semiconductor processing and method for producing semiconductor chip or semiconductor component using same
WO2017179439A1